2020
DOI: 10.34117/bjdv6n8-007
|View full text |Cite
|
Sign up to set email alerts
|

Influência De Hidrogel Em Caracteres Fitotécnicos Da Soja

Abstract: O déficit hídrico durante a germinação de sementes e o estabelecimento da cultura da soja pode acarretar prejuízos agronômicos. O objetivo da realização deste trabalho foi avaliar a influência dos polímeros hidroabsorventes ou hidrogéis, nos caracteres fitotécnicos da cultura da soja em sistema de semeadura direta (SSD), num LATOSSOLO VERMELHO Eutroférrico. O delineamento utilizado foi em blocos casualizados (D.B.C.), com quatro repetições, em esquema fatorial 2 x 5 + 1, com fontes dos polímeros (Polim-Agri PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…However, high hydrogel rates not always have positive responses from some soybean variables (Mendonça et al, 2013). Abraão et al (2020) found that the hydrogel rate of 20 kg ha -1 increased the number of plants in approximately 4%. Gales et al (2012) found increases in soybean yield subjected to application of hydrogel, confirming the results found for the hydrogel treatments combined with potassium topdressing in the present study.…”
Section: Experiments Ii: Soybeanmentioning
confidence: 98%
“…However, high hydrogel rates not always have positive responses from some soybean variables (Mendonça et al, 2013). Abraão et al (2020) found that the hydrogel rate of 20 kg ha -1 increased the number of plants in approximately 4%. Gales et al (2012) found increases in soybean yield subjected to application of hydrogel, confirming the results found for the hydrogel treatments combined with potassium topdressing in the present study.…”
Section: Experiments Ii: Soybeanmentioning
confidence: 98%